(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Retinopathy of Prematurity (ROP) is a disease process mostly reported in preterm and Low Birth Weight (LBW) neonates. Early detection of ROP in these groups and identification of associated neonatal factors and their prevention can prevent wide range of visual morbidity from impairment of vision to blindness in later life. The aim of this study was to determine prevalence of ROP and to identify neonatal risk factors for the development of ROP in preterm and LBW infants. Materials and methods: A total of 105 LBW infants weighing <2000 gm and/or with a Gestational Age (GA) <35 weeks and more mature and heavier neonates with eventful neonatal period were enrolled in the study.Infants were subjected to eye examinations at 4 (±1) weeks after birthby experienced ophthalmologist trained in ROP. Results: Out of 105 study population, ROP was found in 24 infants (22.9%):2 had stage 2 (25.0%), 17 had stage 3 (70.8%), 1 had stage 5 (4.2%) ROP. Two (8.4%) had Aggressive Posterior Retinopathy of Prematurity (APROP) and 3 (12.6%) had plus disease. On univariate analysis LBW, lower GA, female sex, apneic spell, sepsis, Prenatal Asphyxia (PNA) blood transfusion, longer duration of oxygen therapy and longer stay in hospital were found to be significant. On logistic regression analysis lower GA and female sex was found to be the independent factor for development of ROP. Conclusion: To control blindness due to ROP the study suggested that all preterm infants weighing £1500gm and the GA of £32 weeks should be screened at 4 weeks post-natal age. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 4-8